Pendelegasian Kewenangan Pemerintah Daerah kepada Kecamatan dan Kelurahan dalam Rangka Memperkuat Otonomi Daerah - Tri Widodo W. Utomo (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2018)
Recently the demand to assign the authority of district/municipality to the sub districts and villages is ever-increasing. This is not merely a need, but rather it has been a must to promote the effectiveness and efficiency of local autonomy implementation. However, there is an indication that the authority handed over is not implemented optimally. The apparent weaknesses are among others instigated by the imprecision of authority approach and pattern used, and other technical reasons such as the lack of resource distribution concept, implementation and technical procedures, etc. Other crucial factors hindering the implementation of the autonomy policy are the obscurity of the criteria to determine the authority to be assigned, and the local organizational structure of sub district which is forced to accept and implement the regional authority. Based on the various problems as discussed above, this essay tries to analyze and evaluate the practice of authority delegation from the head of district/municipality to the heads of sub districts and villages, and to offer some essential policy alternatives